The Oxford handbook of multimethod and mixed methods research inquiry - Hesse-Biber, Sharlene Nagy; Johnson, Burke (Oxford library of psychology., 2015)
"The Oxford Handbook of Multi and Mixed Methods Research Inquiry is designed to offer a range of innovative knowledge- building perspectives and methods tools with the goal of enhancing new ways of asking and addressing complex research questions. The Handbook offers multiple quantitative and qualitative theoretical and interdisciplinary visions and practice. Each chapter is written in clear and concise language by leading scholars in the field. The Handbook reflects the most current thinking and scholarship on emerging multi and mixed methods research inquiry within and across the disciplines. The Handbook aims to become an exceptional, timely, and critical research benchmark. It addresses interdisciplinary and complex questions that traverse a range of research communities both in and outside the academy, and its empirical focus demonstrates the synergistic of multi and mixed methods research inquiry for answering complex research questions"--Publisher's website